(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
This paper focuses on the use of Herringbone Technique for Improving Reading Comprehension Skill. The purpose of this research was to find the significance of using Herringbone technique for Improving Students’ Reading Comprehension Skill at the Eleventh Grade of Social Science Two in SMAN 21 Makassar. This research used a quantitative method with pre-experimental research approach. Sampling technique was used to collect data. The population of this research was all the eleventh grades of social science two in SMAN 21 Makassar. The total sample was 35 students. The instruments of this research were test and questionnaire. In collecting data, the test aims to find the significance using Herringbone Technique, while the questionnaire aims to find out the students’ obstacles in using Herringbone Technique. The result showed that there was difference mean score between pre-test and post-test. The mean score in pre-test was 63,77% and in post-test 87,77%. It was indicated that the mean has increase 24%. It can be seen that the improvement of the students’ mean score in the post-test was higher than pre-test. The result of questionnaire showed that there were no obstacles that students feel through this method. It can be seen from the question no. 7 “I feel bored reading English text using the Herringbone technique” and the data showed 48,7% of students choose uncertain, 45,71% of students choose disagree, 2,86% of students choose agree. From the questionnaire results, some students tend no problem using Herringbone technique for improving reading comprehension skill.